Graphene derived carbon confined sulfur cathodes for lithium-sulfur batteries: Electrochemical impedance studies. (1st October 2016) - Ganesan, Aswathi; Varzi, Alberto; Passerini, Stefano; Shaijumon, Manikoth M.
Graphical abstract: Highlights: Graphene-derived carbon (GDC) with distinctive porosity characteristics are prepared. Effect of micro-/mesoporosity of GDC for improved Li-S battery performance is studied. Impedance studies reveal insights into Li-S redox reactions and capacity fading phenomena. Abstract: Sulfur nanocomposites are prepared by using graphene derived carbon (GDC), with controlled porosity characteristics, as confining matrix and are studied as efficient cathodes for lithium-sulfur (Li-S) batteries. To understand the effect of micro-/mesoporosity in porous carbon for the effective encapsulation of sulfur and polysulfides towards improved Li-S battery performance, two different GDC samples with controlled porosity characteristics, one with predominantly micropores (GDC-1) and a surface area of 1970 m 2 g −1 and the other with a surface area of 3239 m 2 g −1, having more or less equal contribution of micro- and mesopores (GDC-2), are used to synthesize nanocomposite sulfur electrodes following melt diffusion process. Electrochemical studies are carried out by using cyclic voltammetry, galvanostatic charge/discharge cycling and electrochemical impedance spectroscopy (EIS). EIS spectra collected at different depth of discharge (DOD) in the first cycle as well as upon cycling give valuable insights into the Li-S redox reactions and capacity fading phenomena in these electrodes. The impedance response of GDC-S electrodes suggests a detrimental effect of the mesopores, where insoluble reaction products can easily accumulate, resulting in the loss of active material leading to capacity fading of Li-S cells.